The ASP and C5L2 pathway: another bridge between inflammation and metabolic homeostasis. (June 2010) - Fisette, Alexandre; Cianflone, Katherine
Hormones secreted from the adipose tissue, termed adipokines, have been extensively studied in the past two decades and this work has triggered a paradigm shift. Previously considered to be a passive organ exclusively devoted to storage, adipose tissue is now seen as a major endocrine modulator of energy homeostasis. Acylation-stimulating protein (ASP) is one of these adipokines and it interacts with its receptor C5L2 to induce several anabolic effects. Both ASP and C5L2 are also closely linked with the immune system. However, few studies have examined the duality of roles observed with ASP and C5L2. This article aims to demonstrate the potential roles of ASP and C5L2 in metabolic homeostasis and inflammation and to discuss the relationships of these two parallel systems.